O governo da lua: relação natureza e cultura no contexto da política nacional de gestão ambiental e territorial nos Xacriabá - Helen Dayane Rodrigues Santa Rosa (2017)
This dissertation seeks to highlight the views on the relation between nature and culture in the Xakriabá Society discussed during the implementation of the National Policy of Environmental and Territorial Management in Indigenous Lands (PNGATI). Based on an ethnographic approach, a methodology was used to analyze the final documents of the Territorial and Environmental Management Plan, the testimony of the indigenous people who participated in this process - articulated to guided walks by indigenous connoisseurs. Taking as a perspective a relationalreading from the temporalities Aforetime, Time of the Ancient and Time of Now and their respective territorialities verified throughout the Xakriabá historicity, the Secret, the Sacred and the Science were identified like immutable bases of the Xakriabá cosmology that operate underdifferent systems such as the Moon Government and the nature that transmits warnings. Having examined the different conceptions of nature and culture evidenced during the implementation of the PNGATI, considering the views of the actors involved in the Policy, it was possible to verify that the native parameters do not coincide with the national technical-scientific parameters. They are, therefore, ruled by different logics and orders.